Distance-to-well effects on plant community based on palatability and grazing tolerance in the desert-steppe of Mongolia - Narantsetseg, Amartuvshin, author; Kang, Sinkyu, author; Ko, Dongwook, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
Wells in grasslands are usually accompanied with increased traffic by humans and livestock. The purpose of this study was to detect whether plant community structure differs in spatial arrangement with different grazing gradients in the desert steppe of Mongolia. We found poor correlation between total coverage and distance-to-well in big-shrub and shrub-limited sites but strong correlation in the small-shrub site. Dominance of palatable plants along the transect appeared in the big-shrub site but that of palatable, grazing avoider and grazing tolerant plants appeared in other two sites. The results show that these communities might respond differently to grazing pressure. Livestock trampling was limited to near the well and then grazing might be effective far from the well, because all sites showed dominance of palatable herbaceous plants. Sub-dominance of Eurotia ceratoides appeared nearest to the well and followed Caragana spp. sub-dominance. Ajania spp. sub-dominance appeared more away than E. ceratoides and Caragana spp. Dominance of palatable herbaceous plants appeared near the well, compared with that of shrubs. In all sites, palatable herbaceous plant community was replaced by grazing tolerant plant community near the well and shrubs disappeared. This indicates that succession after grazing might be faster in herbaceous plant community than shrub one.
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: grazing; trampling; palatable plant; grazing tolerant plant